Use of Sulla flexuosa (Hedysarum flexuosum) by breeders in Kabylia (Algeria) - Zirmi-Zembri N.; Kadi S.A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Hedysarum flexuosum (Sulla flexuosa) is a forage legume endemic to North Africa and south of Europe. Unfortunately, although its nutritional value, equal or even higher than alfalfa, this resource is classified as endangered because it spontaneously grows and is not cultivated. However, it could play a leading role in the resorption of the fodder deficit in Algeria. In order to contribute to the conservation of Sulla flexuosa, the collection of information on the uses of this legume by the populations is one of the most important stages. For this, from April to May 2018, an investigation focusing on the use of this legume was carried out by individual interviews of 105 breeders spread throughout the Tizi-Ouzou region in Algeria. The Sulla is reported in about twenty communes (districts) across the wilaya (region) where its appearance is mostly noticed by farmers in December (19.8%) or February (20.7%). For half of the breeders, Sulla grows mainly on sloping ground. While the vast majority (84%) distinguish between the two forms (plagiotropic or orthotropic), only about half (45.3%) maintain that it is biennial and nearly one-third (34%) think it is annual. It is the totality of the breeders who uses it in animal feeding and which signal its use also in human food. In animal feed, three quarters of breeders use it as green (feeding to the trough or pasture). The combination of the scientific research results combined with traditional and ancestral knowledge must be the basis of all breeding and genetic improvement programs leading to domestication of H. flexuosum.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)